Characterization and Management of Glyphosate- and HPPD-Inhibitor-Resistant Palmer Amaranth in Kansas Corn Production - V. Kumar; R. Liu; T. Lambert (Kansas Agricultural Experiment Station Research Reports, 2019)
Multiple herbicide-resistant (MHR) Palmer amaranth is an increasing management concern for Kansas grain producers. The main purpose of this research was to 1) characterize the resistance levels to glyphosate (Roundup PowerMax) and mesotrione (Callisto) in an MHR Palmer amaranth population collected from Stafford County, KS, compared to a known herbicide-susceptible (SUS) population; and 2) to evaluate the effectiveness of preemergence (PRE), PRE followed by (fb) early post emergence (EPOST), and PREfblate POST (LPOST) herbicide programs for controlling this MHR population in Roundup Ready and LibertyLink corn. To achieve these objectives, a whole plant dose-response study was conducted in a greenhouse at the Kansas State University Agricultural Research Center near Hays, KS; and a field study was conducted in Stafford County, KS (from where the MHR population was originally collected). Dose-response study indicated that the MHR population had 7.2- and 3.5-fold resistance to glyphosate and mesotrione, respectively, on the basis of visual control (LD50 values). Results from field study indicated that PRE application of Clarity + Acuron in combination with Aatrex, Callisto, Dual II Magnum, or Sencorfba sequential EPOST application of Acuron alone or in combination with Aatrex, Callisto, or Dual II Magnum provided 80 to 95% control of MHR Palmer amaranth population in corn throughout the season. Furthermore, control with PRE applied Clarity + Acuronfba LPOST application of Acuron + Status or Acuron + Liberty averaged 85% at the final rating. Based on these results, the tested Palmer amaranth population from Stafford County has evolved multiple resistance to glyphosate and mesotrione. Two-pass herbicide programs, including PREfbEPOST or LPOST investigated in this research can provide adequate control of this population throughout the season in Roundup Ready and LibertyLink corn.
Keywords: glyphosate; HPPD inhibitors; multiple herbicide resistance; Palmer amaranth